Comparison of Video Laryngoscopy Versus Conventional Laryngoscopy in Anticipated Difficult Intubation in Patients Undergoing Thyroid Surgery: Video Laryngoscopy Versus Conventional Laryngoscopy in Anticipated Difficult Intubation - Riaz, Umaima; Majeed, Zeeshan; Sadaf, Sairah; Ahmed, Adeel; Abbas, Farah; Jamil, Muhammad Irfan (Pakistan Journal of Health Sciences, 2026)
Anticipated difficult airway in thyroid surgery is associated with failed intubation, hypoxia, and airway trauma, despite structured preoperative assessment. Objectives: To compare video laryngoscopy with conventional direct laryngoscopy in adult patients undergoing elective thyroid surgery with anticipated difficult intubation in terms of first- attempt and overall tracheal intubation success, glottic visualization, intubation time, and immediate oropharyngeal injury. Methods: A randomized controlled trial was conducted in the Department of Anesthesia, Sheikh Zayed Hospital, Rahim Yar Khan, from January 2025 to June 2025. Sixty patients (18–60 years) undergoing elective thyroidectomy with anticipated difficult intubation (ASA I–II, ≥1 airway predictor) were enrolled by non-probability consecutive sampling and randomized (1:1) to conventional laryngoscopy or video laryngoscopy. All intubations were performed by experienced anesthetists. Results: Among 60 randomized patients, baseline age (44.47 ± 7.66 vs 44.60 ± 8.02 years) and gender distribution (46.7 % vs 40.0 % males) were comparable between conventional and video- laryngoscopy groups. Video laryngoscopy improved Cormack–Lehane grade I view frequency (60.0% vs 13.3%, p=0.002) and increased first-attempt intubation success (93.3% vs 60.0%, p=0.002). Overall success was 100.0% with video laryngoscopy versus 93.3% with direct laryngoscopy (p=0.150). Mean intubation time was longer with video laryngoscopy (45.13 ± 8.38 vs 39.20 ± 9.83 seconds, p=0.015). Immediate oropharyngeal injury was numerically lower with video laryngoscopy (6.7% vs 20.0%, p=0.129). Conclusions: In anticipated difficult airways during thyroid surgery, video laryngoscopy significantly improved first-attempt intubation success and glottic visualization, while overall success remained similarly high in both groups.